Hydroxyurea mitigates diabetic kidney disease through mTOR-S6K signaling pathway in STZ-induced diabetic mice - Cheng, Wanying; Wang, Cenzhu; Ma, Meican; Zhou, Yu (Frontiers in Cell and Developmental Biology, 2025)
BackgroundDiabetic kidney disease (DKD) is the leading risk factor for end-stage renal disease (ESRD). Hydroxyurea (HU), a sickle cell disease (SCD) drug approved by FDA, shows protective effect in nephropathy. This study aims to understand whether the application of HU could be effective to treat DKD.MethodsThe streptozotocin (STZ)-induced diabetic mice, and high glucose (HG)-treated human renal mesangial cells (HRMCs) were used to investigate the effect of HU on DKD. Serum creatinine and blood urea nitrogen levels reflecting renal function were evaluated. Histology was used to evaluate pathological changes. Indicators of inflammation and apoptosis were detected. Lastly, the mTOR-S6K pathway was explored by detecting the protein expression of S6K and phosphorylated S6K.ResultsIn STZ-induced diabetic mice, administration of HU (20 mg/kg) in drinking water for 16 weeks resulted in significant reductions in creatinine and urea nitrogen levels, alongside mitigating histopathological damage. Additionally, HU effectively suppressed the inflammatory response and apoptosis within the kidneys. HRMC cells were cultivated in HG conditions, and HU effectively attenuated the HG-induced inflammation and apoptosis. Moreover, HU treatment significantly inhibited the mTOR signaling pathway in both in both in vivo and in vitro experiments.ConclusionThis study unveils a new role of HU in alleviating diabetic kidney disease by modulating inflammation and apoptosis through the mTOR-S6K pathway. However, since HU did not significantly affect blood glucose levels, its therapeutic potential may be best realized when used in combination with standard antidiabetic therapies. Such a combination approach could simultaneously address hyperglycemia and renal dysfunction, offering a more comprehensive management strategy for DKD.